Combining multiple tactics over time for cost‐effective eradication of invading insect populations. (9th November 2020) - Lampert, Adam; Liebhold, Andrew M.
Abstract: Because of the profound ecological and economic impacts of many non‐native insect species, early detection and eradication of newly founded, isolated populations is a high priority for preventing damages. Though successful eradication is often challenging, the effectiveness of several treatment methods/tactics is enhanced by the existence of Allee dynamics in target populations. Historically, successful eradication has often relied on the application of two or more tactics. Here, we examine how to combine three treatment tactics in the most cost‐effective manner, either simultaneously or sequentially in a multiple‐annum process. We show that each tactic is most efficient across a specific range of population densities. Furthermore, we show that certain tactics inhibit the efficiency of other tactics and should therefore not be used simultaneously; but since each tactic is effective at specific densities, different combinations of tactics should be applied sequentially through time when a multiple‐annum eradication programme is needed. Abstract : When attempting to eradicate invading insect populations, a major question is how to optimally combine multiple tools/tactics. Here we show that mating disruption and sterile male release should not be used simultaneously, but each of these tactics may need to be used in different years during a multiple‐annum eradication process.